2004
DOI: 10.1007/s10725-004-5935-3
|View full text |Cite
|
Sign up to set email alerts
|

Co-regulation Of ear growth and internode elongation in corn

Abstract: Ear is the harvest part of corn (Zea mays L.) and we are interested in studying its growth and development in our effort in corn yield improvement. In our current study, we examined the relationship between ear growth and internode characteristics using different approaches. Correlations between stem growth rate and number of ears per plant (prolificacy) were assessed among several genotypes. Internode elongation of 2 genotypes was modified by plant hormones and by population density manipulations. Among the 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…At Garden City, compensation in the ears plant -1 yield component occurred as late as the V11 growth stage when under conditions of 75% stand removal (Table 1). Xu et al (2004) reported that even for non-prolific hybrids, the ears plant -1 yield component did not become completely fixed until between V11 and R2.…”
Section: Discussionmentioning
confidence: 99%
“…At Garden City, compensation in the ears plant -1 yield component occurred as late as the V11 growth stage when under conditions of 75% stand removal (Table 1). Xu et al (2004) reported that even for non-prolific hybrids, the ears plant -1 yield component did not become completely fixed until between V11 and R2.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Xu et al. () found an increase in cob size when UCZ was applied at early growth stages, pointing to the impact of application time on yield performance. The application of PAC always resulted in shorter internodes and reduced plant height (Dale & Drennan, ; Iremiren, Adewumi, Aduloju, & Ibitoye, ; Khalil & Rahman, ).…”
Section: Introductionmentioning
confidence: 90%
“…Hormone levels, particularly of GAs in maize, affect flower sexuality (Bortiri & Hake, ; Irish, ). High levels of GA induce feminine characteristics, whereas in the semi‐dwarf mutants with low GA levels, masculine structures are favoured (Irish, ; Rood, Pharis, & Major, ; Schluttenhofer, Massa, & Mitchell, ; Xu, York, Miller, & Cheikh, ). The abnormalities in maize flowers could be overcome by a non‐constitutive modification of GA concentrations in the vegetative tissues while leaving GA in the reproductive organs unaffected (Xu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…High plant density is a good strategy to obtain high yield [7,8] to meet the current and future food necessities of high population and their rising dietary needs [9]. Improvement in corn yield is dependent on its genetic characteristics, morph-physiological behaviour and its interaction with the environment [10]. Increasing the population density of plants is an agronomical practice that has continuously been studied for maize crops (Table 1).…”
Section: Introductionmentioning
confidence: 99%